External dose assessment in the Ukraine following the Chernobyl accident - Frazier, Remi Jordan Lesartre, author; Borak, Thomas, advisor; Brandl, Alex, committee member; Harton, John, committee member (Colorado State University. Libraries, 2014)
While the physiological effects of radiation exposure have been well characterized in general, it remains unclear what the relationship is between large-scale radiological events and psychosocial behavior outcomes in individuals or populations. To investigate this, the National Science Foundation funded a research project in 2008 at the University of Colorado in collaboration with Colorado State University to expand the knowledge of complex interactions between radiation exposure, perception of risk, and psychosocial behavior outcomes by modeling outcomes for a representative sample of the population of the Ukraine which had been exposed to radiocontaminant materials released by the reactor accident at Chernobyl on 26 April 1986. In service of this project, a methodology (based substantially on previously published models specific to the Chernobyl disaster and the Ukrainian population) was developed for daily cumulative effective external dose and dose rate assessment for individuals in the Ukraine for as a result of the Chernobyl disaster. A software platform was designed and produced to estimate effective external dose and dose rate for individuals based on their age, occupation, and location of residence on each day between 26 April 1986 and 31 December 2009. A methodology was developed to transform published 137Cs soil deposition contour maps from the Comprehensive Atlas of Caesium Deposition on Europe after the Chernobyl Accident into a geospatial database to access these data as a radiological source term. Cumulative effective external dose and dose rate were computed for each individual in a 703-member cohort of Ukrainians randomly selected to be representative of the population of the country as a whole. Error was estimated for the resulting individual dose and dose rate values with Monte Carlo simulations. Distributions of input parameters for the dose assessment methodology were compared to computed dose and dose rate estimates to determine which parameters were driving the computed results. The mean external effective dose for all individuals in the cohort due to exposure to radiocontamination from the Chernobyl accident between 26 April 1986 and 31 December 2009 was found to be 1.2 mSv; the geometric mean was 0.84 mSv with a geometric standard deviation of 2.1. The mean value is well below the mean external effective dose expected due to typical background radiation (which in the United States over this time period would be 12.0 mSv). Sensitivity analysis suggests that the greatest driver of the distribution of individual dose estimates is lack of specific information about the daily behavior of each individual, specifically the portion of time each individual spent indoors (and shielded from radionuclides deposited on the soil) versus outdoors (and unshielded).
Keywords: Chernobyl; dosimetry; dose reconstruction